PREDICTION QUANTITIES OF AVAILABLE OF CAPITA CONSUMPTION OF RED MEAT, CHICKEN AND FISH IN IRAQ FOR PERIOD 2012-2022 THROUGH USING BOX - JENKINS METHODOLOGY. - & Jabra, Mageed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The aim of this paper is to analyze time series using the method of Box and Jenkins (B&J) (diagnosit, estimating, model appropriate test and prediction) to find the best model of predicting available quantities for red meat, chicken and fish consumption in Iraq depending on the annual data of 1990 – 2012. The analysis results showed that the model was the appropriate model for red meat of (0, 1, 1), for chicken of (1, 1, 1) and for fish of (1, 0, 0). Annually predicting available quantities for red meat, chicken and fish consumption was depending on these models for 2012 – 2022. The rates of available quantities growth for red meat, chicken and fish consumption per capita decreased during the studied period and were compatible with predicted quantities which indicated the decreasing but slowly. To keep on the current levels of red meet, chicken and fish consumption. It must be working on increasing the development of these sections of 1.9 , 1.45 , and 1.6%, respectively, to face the predicted negative development rate of -1.9 , -1.4 and -1.6% , respectively.